Assessing the Impact of Digital Transformation on Human Resource Management in Nigerian Tertiary Institutions: A Measurement Model (Digital HRM Impact Assessment Framework (DHIAF)) Proposal - Asabor, Mary Bivwiere; Alordiah, Caroline (NIU Journal of Humanities; Vol. 10 Núm. 2 (2025): NIU Journal of Humanities, Vol. 10 No. 2, June 2025, 2025)
The digital transformation of Human Resource Management (HRM) practices has become imperative for enhancing administrative efficiency, service delivery, and institutional competitiveness within Nigerian tertiary institutions. This study introduces the Digital HRM Impact Assessment Framework (DHIAF), an integrative model that combines the Technology Acceptance Model (TAM), Diffusion of Innovation Theory, Resource-Based View (RBV), and Socio-Technical Systems Theory to holistically assess the impact of digital HRM initiatives. The framework delineates five core dimensions: Recruitment and Selection, Training and Development, Performance Management, Employee Engagement and Communication, and HR Administrative Efficiency. Each dimension encompasses specific sub-dimensions and indicators designed to capture the multifaceted effects of digitalization on HRM processes. The study also proposes a theoretical validation approach, including pilot testing and factor analyses, to ensure the reliability and validity of the measurement model. The discussion highlights anticipated benefits such as improved efficiency and service delivery, while acknowledging potential challenges like technological infrastructure deficits and resistance from non-tech-savvy staff. Policy implications underscore the need for national mandates on digital HRM adoption, capacity-building programs, and strategic partnerships with technology providers. The study concludes by emphasizing the necessity of strategic planning, leadership commitment, and sustained investment to successfully navigate the digital transformation of HRM in Nigerian universities.​ Keywords: Digital HRM; Nigerian tertiary institutions; Human Resource Management; Digital transformation; Technology Acceptance Model; Measurement model.